PENERAPAN MODEL KOOPERATIF TIPE THINK PAIR SHARE BERBANTUAN MEDIA FLIPBOOK DALAM MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS IV SEKOLAH DASAR - Sintia Ulhaq; Neneng Sri Wulan; Wina Mustikaati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was carried out due to the low reading comprehension ability in grade IV students. The purpose of this study is to find out how teachers and students are doing, as well as measure students' reading comprehension skills after the application of the Think Pair Share type cooperative learning model with the help of Flipbook media on fable story material. This research was conducted in grade IV consisting of 27 students, with a composition of 15 male students and 12 female students. The method used is Classroom Action Research (PTK) which is carried out in two cycles, each consisting of one meeting. The instruments used in data collection include observation, tests, and documentation. The results showed that in the first cycle, only 4 students achieved learning completeness with an average class score of 60.25. In cycle II, the number of students who completed increased to 24 students, with the average class score increasing to 79.11. Thus, the application of the Think Pair Share type cooperative model supported by Flipbook media has been proven to have a positive impact on improving the reading comprehension ability of grade IV students. The researcher suggests that future research use media that attracts students' reading interest more and pays special attention to reading comprehension indicators whose achievement is still low.